Comparison of quantitative computed tomography and dual-energy X-ray absorptiometry in elderly patients with vertebral and nonvertebral fractures: Preliminary results - Derin Çiçek, Esin; Öztürk, Gülcan; Aktaş, İlknur (Journal of Surgery and Medicine, 2020)
Aim: Dual-energy X-ray absorptiometry (DXA) and quantitative computed tomography (QCT) are methods used today to evaluate bone mass and structure and determine the risk of fractures. In this study, spinal and femoral bone density results measured by DXA and QCT in elderly patients with vertebral and non-vertebral fractures were compared to identify the most effective method in determining the risk of osteoporosis and fractures. Methods: In this retrospective cohort study, 45 elderly patients aged 65–84 years were analyzed. Group 1 included 11 patients with atraumatic vertebral fractures, Group 2 included 11 patients with non-vertebral fractures and Group 3 included 23 patients without fractures. T-scores and bone mineral density (BMD) values of spinal (lumbar 1-4) and femoral (neck) regions measured by both DXA and QCT were evaluated. Results: Spinal and femoral T-scores and BMD values measured by DXA and QCT were similar between the groups (P>0.05 for all). In Group 1, lumbar BMD value, lumbar and femoral neck T-scores measured by QCT were significantly lower than DXA (P<0.001, P=0.004 and P=0.037, respectively). In Group 2, lumbar BMD value and T-score measured by QCT were significantly lower than DXA (P<0.001 and P<0.001). In Group 3, lumbar T-score, lumbar and femoral neck BMD values measured by QCT were significantly lower than DXA (P<0.001, P<0.001 and P=0.004, respectively). Conclusion: QCT is an effective method that can be used in elderly patients with fractures and arthrosis where DXA may yield false-positive results.